ANALISIS KADAR RADHA’AH YANG MENGHARAMKAN PERNIKAHAN PERSPEKTIF EMPAT MAZHAB - Hifdhotul Munawaroh; Yana Elita; Andini Rachmawati; Nida Farida Ramadani (Journal of Indonesian Comparative of Syari'ah Law, 2025)
There are differences of opinion among the four madhhabs of Shafi'i, Hanafi, Maliki and Hanbali regarding the amount of breastfeeding that causes a mahram relationship and the method of breastfeeding. Therefore, this study focuses on two main aspects first, analysing the opinions of the four madhhabs regarding the level of radha'ah and the method of breastfeeding that prohibits marriage second, identifying the similarities and differences in the views of the Mazdahib Imams regarding this matter. This research uses qualitative research and is conducted through literature studies that refer to primary and secondary legal materials. The author's type of research is a normative fiqh approach with a comparative approach. The results of the study confirm that the four madhhabs agree that the mahram relationship due to breastfeeding is not only limited to direct breastfeeding, but also includes other methods, such as breastfeeding through bottles, aids, or even through the nose, as long as the milk enters the baby's body and has a growth effect.